THE INFLUENCE OF GEOGRAPHICAL OF GEOGRAPHICAL CLOSENESS INTO POLITENESS STRATEGIES AND FTAs IN INTERCULTURAL COMMUNICATION: INTERCULTURAL COMMUNICATION Yosi Handayani, yosi@polibatam.ac.id, Politeknik Negeri Batam - Yosi Handayani (Universitas Putera Batam, 2014)
Hall in Lauring (2011, p. 233) states that ‘culture is communication and communication is culture’. People from different cultural background have different way of maintaining the relationship between speakers and hearers. Brown and Levinson (1987) believe that culture and politeness have significant effect toward the success of communication. They add that people need to show their awareness of other people’s face want, public self-image. The hearers from some cultures are often imposed by the speakers from another culture since each culture has its own standard and value in categories the politeness. However, people come from two area which are geographically close often get no problem with politeness strategies when they have communication. Their geographic closeness make them easy to adopt and understand the culture, and then each of them know how to communicate in order not to threaten the hearers’ face. Therefore, this essay intends to discuss about the comparison between politeness strategies in two cultures which are geographically close, Chinese and Japanese. It is assumed that those cultures can be closely related one to another because of the geographical position. In addition, the essay also discuses about the politeness strategy differences between two cultures which are geographically not close. In this term, the writer compares Chinese/Japanese and western cultures, especially English speaking countries. Moreover, the discussion also includes the explanation on how FTAs can occur in intercultural communication between Chinese, Japanese, and English speakers.